2022
DOI: 10.1021/acs.inorgchem.2c02461
|View full text |Cite
|
Sign up to set email alerts
|

Copper Iodide Cluster Incorporated Luminescent Organic–Inorganic Hybrid Coating Exhibiting Both Corrosion Protection and Antibacterial Properties

Abstract: A photoluminescent organic−inorganic hybrid coating is synthesized by the incorporation of an emissive Cu 4 I 4 core into a cross-linked coating network through Cu−P coordination bonds. The hybrid coating not only emits strong yellow emission under UV-light irradiation but also exhibits corrosion protection of the metallic surface. Moreover, bactericidal properties are studied that were first reported for Cu 4 I 4 -based hybrid light-emitting materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…In addition to the well-documented intriguing photophysical and optoelectronic properties [11] we speculate that such clusters could also serve as antimicrobial coating precursors, potentially matching or even exceeding the efficacy of their parental CuI nanoparticles. [12] To prepare the coating, fresh crystallites of the cluster were dissolved in tetrahydrofuran (THF) at desired concentrations. The solution was then directly drop-cast onto cotton fabric swatches, followed by drying at ambient conditions (Figure 1a and 1b).…”
Section: Coating Design and Fabricationmentioning
confidence: 99%
“…In addition to the well-documented intriguing photophysical and optoelectronic properties [11] we speculate that such clusters could also serve as antimicrobial coating precursors, potentially matching or even exceeding the efficacy of their parental CuI nanoparticles. [12] To prepare the coating, fresh crystallites of the cluster were dissolved in tetrahydrofuran (THF) at desired concentrations. The solution was then directly drop-cast onto cotton fabric swatches, followed by drying at ambient conditions (Figure 1a and 1b).…”
Section: Coating Design and Fabricationmentioning
confidence: 99%
“…Connecting PMOFs with inorganic semiconductors via covalent bonds to form the heterojunction is an effective method to solve the above problems and also collect the unique energy band structure adjustment advantages of inorganic materials. Such chemically bonded interaction between the organic materials and other components has been utilized to enhance the electron transfer during the photocatalytic CO 2 reduction or immobilize molecular catalysts on heterogeneous materials. As reported by Ouyang’s group, the combination of copper atoms and organic ligand molecules resulted in novel properties that the original pure component does not possess . Recently, Ma’s group successfully constructed the UiO-66-NH 2 (Zr/Ti)/carboxyl-functionalized MXene composite through the auxiliary coordination approach, which showed a 20 and 4 times higher hydrogen evolution reaction (HER) activity than that of UZT and UiO-66-NH 2 (Zr/Ti)/MXene, respectively .…”
Section: Introductionmentioning
confidence: 99%
“…39−44 As reported by Ouyang's group, the combination of copper atoms and organic ligand molecules resulted in novel properties that the original pure component does not possess. 45 Recently, Ma's group successfully constructed the UiO-66-NH 2 (Zr/Ti)/carboxyl-functionalized MXene composite through the auxiliary coordination approach, which showed a 20 and 4 times higher hydrogen evolution reaction (HER) activity than that of UZT and UiO-66-NH 2 (Zr/Ti)/ MXene, respectively. 46 In addition, Xu's group reported that the strong chemical bond between the MOF and rGO favored the adsorption and K + transport compared to the physical mixture of MOF and rGO.…”
Section: Introductionmentioning
confidence: 99%